Analisis Sebaran Potensi dan Pemasaran Rempah di Provinsi Gorontalo - Hasnianti S Yusup; Amelia Murtisari (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Gorontalo Province is part of the spice route in Indonesia and has a wealth of hidden natural resources such as candlenut and cingkeh, which dominate, but research related to spices in Gorontalo has not been widely explored. At the same time, spice products are part of the people's livelihood in Gorontalo Province. As an effort to maintain this potential, it is necessary to conduct research to know how is the potential distribution of spices (candlenut, cloves, nutmeg, cinnamon, and turmeric) in Gorontalo Province and how is the marketing channel of spices (candlenut, clove, nutmeg, cinnamon, and turmeric) in Gorontalo Province. This research was conducted from January to May 2024. The research location was in Gorontalo and Bone Bolango districts. The qualitative research method uses a structured questionnaire to obtain primary data. In contrast, secondary data is obtained through relevant agencies such as the Central Bureau of Statistics, the Agriculture Office, and literature studies of scientific journals and books. The research variables include the amount of production, price, spice potential, spice location distribution points, and spice marketing channels. The sampling technique was purposive sampling. The samples were ten candlenut farmers, ten cingkeh farmers, three nutmeg farmers, two cinnamon farmers, and three turmeric farmers. The result of the study is the distribution of candlenut in Biluango Village, Bone Bolango Regency, while in Gorontalo Regency is the distribution point of clove (North Dulamayo), nutmeg (South Dulamayo), cinnamon (North Dulamayo) and turmeric (South Dulamayo). There are four types of spice marketing channels in Gorontalo Province, including Type 1, from farmers directly to consumers (cinnamon, nutmeg, turmeric); Type 2, from farmers to intermediary traders followed by companies or industries (cloves); Type 3, from farmers to retailers followed by consumers (candlenuts, cinnamon, nutmeg, turmeric); type 4 from farmers to intermediary traders followed by retailers and final consumers (cloves, candlenuts, cinnamon).